Rancang Bangun Pengendali Sistem Pompa Otomatis Pada Penyiraman Tanaman Berbasis Sensor Kelembaban dengan Kendali Arduino - Rajagukguk, Antonius; Simamora, Joel Fernando; Ervianto, Edy (Program Studi Teknik Elektro Universitas Khairun, 2021)
Along with technological advances in modern times, and the development of science, human needs are also growing. In order to facilitate human work, many technologies have been created using automatic systems. One of them is in the case of automatic plant watering for farmers or garden owners. For this reason, the authors carried out a design of automatic plant sprinklers based on the YL-38 type soil moisture sensor which will be controlled by Arduino. Which later will send a duty cycle to the buck converter to change the voltage automatically according to soil conditions which have been grouped into four parts, namely very dry, dry, humid, and wet. Changes in voltage will affect the rotational speed of the motor according to the needs of the ground. With real time watering, the RTC DS1302 type is used so that this watering will be more scheduled. This watering uses a supply from a 12 volt DC battery with a 12 volt water pump motor load.